The weekend cook : good food for real life - Hartnett, Angela (Bloomsbury Absolute, 2022)
"An invitation to supper at Angela Hartnett's house is a real treat. Nestled in the middle of Wilkes Street, in London's vibrant East End, you know you're going to get delicious food, great company and a relaxed atmosphere that is as far removed from the high-octane stress of a professional kitchen as it is from the awkward social anxiety that many of us face when hosting a dinner. Angela knows the secrets to throwing the most relaxed and enjoyable dinners for friends and family - sometimes mad, but always magical evenings that people talk about for months afterwards - and in this book she's going to share them. Great flavours and simple recipes abound in these pages, each one a joy to cook and eat, from satisfying one-pot dishes and comforting risottos to perfect party food and bakes to feed a hungry crowd. Collected in these pages are over 100 recipes from one of Britain's most-loved chefs, as well as time saving tips and cheats that will take the stress out of hosting and allow you to enjoy your dinner parties without breaking a sweat. The only essential ingredients are friends and family ... and lots of them."--Provided by publisher.